Congenital Nasal Pyriform Aperture Stenosis: Conservative Management. (October 2013) - Collins, Benjamin; Powitzky, Rosser; Enix, Jessica; Digoy, G. Paul
Objectives: This case series outlines the advantages of using 0.1% intranasal dexamethasone drops (IDD) to treat nasal obstruction in patients with congenital pyriform aperture stenosis (PAS). Methods: Five consecutive cases of PAS were reviewed. Results: Three patients were treated with IDD alone, and 2 were treated surgically and had residual postoperative nasal obstruction before IDD. Four patients in follow-up (mean, 1 year) were weaned off the steroid drops with good breathing results. One patient developed iatrogenic Cushing's disease, and another, who was initially treated with surgery, eventually required nasal vestibular stenosis repair in addition to IDD. Conclusions: This study is the first to review the use of IDD in treating PAS. The potential impact of midnasal stenosis is discussed, and a conservative management algorithm for patients with PAS is presented. Careful surveillance for potential side effects of IDD is recommended, especially in cases that require elevated doses.